The Doctrine of the Mean in the Eudemian Ethics - Zanuzzi, Inara (Revista Archai, 2017)
This paper aims to reconstruct the Aristotelian doctrine of the mean based on some passages from the Eudemian Ethics, books II and III. It is claimed that the mean in actions is prior to the mean in dispositions, and that the correct actions are the ones in a mean because they consist in an appropriate answer to the circumstances for the sake of the right human finality, eudaimonia. In relation to the Aristotelian thesis according to which there is a mean, excess and deficiency wherever there is a continuum, it is claimed that this continuum is formed by the emotions, which are the sensible basis of actions. Nonetheless, it is not true that emotions are prior to actions in terms of moral value.